A tool design to assessed sustainability in the shipping industry - Yiallouros , Nicolas (Τμήμα Εμπορίου, Χρηματοοικονομικών και Ναυτιλίας, Σχολή Διοίκησης και Οικονομίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
ABN AMRO was chosen as the focused banking group in order to examine the philosophy of sustainable investments in the shipping industry. “The sustainability is part of our DNA” coincide with ABN AMRO strategic plan in order to transform their system towards a more future orientated profile where sustainability matters in terms of environmental, social and economical settings. As they stated: “ABN AMRO wants to be a better bank working towards a better world…” noticeably illustrates that ABN AMRO is seeking to find solutions to regain their customers’ trust in a more sustainable manner and thereafter was preferred as the case study of this master thesis (Zalm, 2011). Subsequently in order to evaluate the sustainability performance of an investment in the shipping industry a metric system should be developed and should be in accordance to the existing ones. This evaluation also coincide with the screening processes of banking groups in accordance to the sustainable criteria in order to assess the sustainability of shipping companies. The objective of this paper is to identify and design a tool that facilitates the initial stage assessment processes of banks during the decision‐making activities for sustainable investments in the shipping industry. Thereafter the main objectives of the master thesis paper are: 1. To assess the sustainability regarding shipping and evaluate the current criteria and requirements of sustainability in the shipping industry 2. To developed (from literature and available data) a metric scheme that helps the evaluation of these sustainable investment in order to measure the sustainable performance To recap the author of this paper will try to measure the sustainability in shipping. This will be obtained through the determination of a measured scheme via available literature in order to evaluate the sustainability of banks’ investment strategy.
Keywords: ABN AMRO; Sustainable investments; Shipping industry